A Novel Approach for Shearer Memory Cutting Based on Fuzzy Optimization Method - Xin Zhou; Zhongbin Wang; Chao Tan; Rui Ji; Xinhua Liu (Advances in Mechanical Engineering, 2013)
In order to improve the implement precision of shearer memory cutting, a novel approach based on the coal floor height variation which is taken as a significant factor and fuzzy optimization theory is proposed. The problem of shearer memory cutting is analyzed and the mathematic model is established. Moreover, the key technologies such as fuzzy control model, quantitative factors, and fuzzy control rules are elaborated, and the flowchart of shearer memory cutting method based on fuzzy optimization theory is designed. Finally, a simulation example is carried out and the proposed approach is proved feasible and efficient.